O Trans-Pacific Partnership Agreement na agenda de propriedade intelectual dos Estados Unidos - Menezes, Henrique Zeferino de (2017)
The aim of this paper is to analyze the role of the Trans-Pacific Partnership Agreement (TPP) on the United States intellectual property rights (IP) negotiations. The text covers, more broadly, the country’s negotiating agenda on IP and the specificity of the TPP within the strategy of building wider and more effective global standards.